Solution-focused treatment of domestic violence offenders accountability for change - Lee, Mo Yee.; Sebold, John.; Uken, Adriana (Oxford : Oxford University Press, 2003)
Rates of recidivism for domestic 'batterers' following traditional treatment programs has lent urgency to finding alternative methods. This book describes a cutting-edge approach to treatment, 'solution-focused therapy', that focuses on holding offenders responsible for building solutions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Abusive men -- Counseling of; Abusive men -- Rehabilitation; Group counseling; Solution-focused therapy